1998
DOI: 10.1007/s001670050220
|View full text |Cite
|
Sign up to set email alerts
|

Significance of graft tension in anterior cruciate ligament reconstruction Basic background and clinical outcome

Abstract: The purpose of this paper is to review scientific evidence that graft tension affects remodelling of the autograft in ligament reconstruction. The in situ freezing model of the patellar tendon, an ideal patellar tendon autograft model, demonstrated that subsequent cellular proliferation following fibroblast necrosis reduces the mechanical properties of the autograft. Stress shielding enhances reduction of the strength in the once-frozen patellar tendon. The strength of the patellar tendon also changes dependin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 32 publications
1
46
0
Order By: Relevance
“…In view of rapid histological and mechanical degradation of the PDS braid, we assume that the stress-shielding effect of the braid is mainly restricted to the first 2-6 weeks. Stress-shielding effects have also been seen in other studies [18]. This might be caused by the lack of load on fibroblast stimulation and remodeling.…”
Section: Discussionsupporting
confidence: 53%
“…In view of rapid histological and mechanical degradation of the PDS braid, we assume that the stress-shielding effect of the braid is mainly restricted to the first 2-6 weeks. Stress-shielding effects have also been seen in other studies [18]. This might be caused by the lack of load on fibroblast stimulation and remodeling.…”
Section: Discussionsupporting
confidence: 53%
“…This prestress helps to provide joint stability, but a very high pretension produces an important additional stress in the graft during the knee movement. This may cause problems in revascularization and remodelling during the postoperative healing process (Cyril and Douglas, 1997;Kampen et al, 1998;Tohyama and Yasuda, 1998). Viscoelasticity decreases the tension imposed during surgery until getting the final value after reaching equilibrium.…”
Section: Patellar Tendon Graft After Initial Prestressmentioning
confidence: 97%
“…Mechanical stretch plays important roles in the remodeling process of the tendon graft. The effect of graft tension on remodeling of the autograft in ligament reconstruction was investigated using an in situ freezing model (Tohyama and Yasuda, 1998). Transmission electron micrographs revealed that the number of small diameter fibrils decreased in the stressshielded tendons compared with non-stress-shielded ones.…”
mentioning
confidence: 99%